Analysis Of The Implementation Of Road Safety On The Jombang-Kertosono Arterial Road Section - Mia Nurul Imamah; Nugroho Utomo; Ibnu Sholichin (Syntax Corporation Indonesia, 2023)
According to data from the Jombang Regency Traffic Traffic Unit of December 2022, there were 114 cases of traffic accidents on the Jombang-Kertosono arterial road. Thus, an analysis of road safety is needed on this road section. The author analyzes the application of road safety using the IPA (Importance Performance Analysis) method, the EAN (Equivalent Accident Number) method, and geometric calculations of roads in accident-prone areas. Based on the analysis of the application of road safety using the IPA method, it is known that the main priority attributes in driving safety are traffic signs and road markings as well as sharp turns which are quite dangerous for motorists. Based on the analysis of accident-prone areas using the EAN method, it is known that STA 01+00 – 02+00 has the highest EAN score of 249 accidents. Based on the road geometric review, it is known that the stopping sight distance of STA 01+00 – 02+00 is 46.78 m which when compared to the standard stopping sight distance is not sufficient and is considered less safe. The value of the side freedom area according to the calculation analysis is 5.4 m which is greater than the available E value, which is 4 m, so it is considered less safe. There are 2 suggested bends using the Spiral-Circle-Spiral type and 2 Spiral-Spiral type bends where each of these bends requires widening the average road pavement width of 1 meter to reduce the risk of traffic accidents on bends due to adequate road width.